VD_FINDINFO HC / 2009 / 443 vom 8. Dezember 2009 - VD Tribunal cantonal (2009)
BAIL À LOYER, EXPULSION DE LOCATAIRE, SOUS-LOCATION, RÉSILIATION IMMÉDIATE, DEMEURE DU DÉBITEUR, SOUS-LOCATAIRE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 457 al. 1 CPC, 23 LPEBL, 29 LPEBL